Response optimisation of TiO2-supported bimetallic NiCo catalyst for the cracking and deoxygenation of waste cooking oil into jet-fuel range hydrocarbon fuels under non-hydrogen environment - Goh B.H.H.; Chong C.T.; Milano J.; Tiong S.K.; Cui Y.; Ng J.-H. (Elsevier Ltd, 2025)
Waste cooking oil is a sustainable feedstock that can be utilised to produce biojet fuel via the hydrodeoxygenation process. However, the need for hydrogen for the hydrodeoxygenation process incurs high cost. In the present work, a type of bimetallic catalyst that can deoxygenate and selectively crack free fatty acids under hydrogen-free conditions was developed. The NiCo/TiO2 catalyst was prepared via the impregnation of varying amounts of Ni and Co salts onto TiO2. Optimisation of the production conditions was performed via response surface methodology based on the Box-Behnken experimental design to maximise the deoxygenation and biojet fuel yield. A maximum deoxygenation yield of 83.13 % with 44.5 % biojet fuel selectivity was obtained from the experiment and optimisation based on Box-Behnken design (R2 > 0.9). Incorporation of Ni and Co onto TiO2 reduced the surface area of the catalyst, but active metal dispersion significantly improved the deoxygenation performance and biojet fuel selectivity. The viscosity, flash point, freezing point and net heat of combustion value of the liquid product were within the jet fuel standard specifications. Overall, the study shows the potential of bimetallic NiCo/TiO2 catalyst in waste cooking oil deoxygenation for biojet fuel production. ? 2024 Elsevier Ltd